Influence Self-Regulated Learning on Creative Thinking Skills in Modern Hair Bun Styling Material: Systematic Literature Review - Afifah, Nabila Tri; Maspiyah, Maspiyah; Pritasari, Octaverina Kecvara; Buditjahjanto, I Gusti Putu Asto; Anifah, Lilik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the contribution of Self-Regulated Learning to students’ creative thinking skills in modern hair bun styling through a Systematic Literature Review approach. The urgency of this research lies in the vocational education demand for learners who are not only technically skilled but also capable of demonstrating creativity in solving aesthetic problems and producing original modern hair bun designs. This research employs a Systematic Literature Review guided by the PRISMA 2020 protocol, including identification, screening, eligibility, and synthesis of national and international indexed articles published between 2019 and 2024 related to Self-Regulated Learning and creative thinking skills. The findings indicate that Self-Regulated Learning has a consistently positive influence on creativity, particularly through metacognitive processes such as planning, strategy monitoring, and reflection. Results also highlight key supporting factors, including scaffolding, project-based learning, and digital learning environments, while barriers include limited instructional support and unsupportive learning conditions. The study concludes that integrating Self-Regulated Learning systematically into vocational aesthetic education is essential to enhance students’ creativity and recommends improving scaffolding practices and implementing project-based tasks as effective strategies.